NEW HUMAN RESOURCE MANAGEMENT AND MANAGEMENT STRATEGY IN JAPAN - Philippe Debroux, (Asian Academy of Management Journal, 1996)
Human resource management is not self-contained activity. It has to be considered in terms of related activities as well as broader social and cultural structures including education, training and labour market regulation. The individual components cannot be understood in isolation or changed piecemeal. This is true for the personnel practices of single firms as it is for the roles of workers, management and government interactions at the regional, industry and national levels